Student digital authorship in learning Differential and Integral Calculus in Engineering courses (Revista BOEM, 2024)
Traditionally, the basic cycle of engineering courses is made up of theoretical subjects in Calculus and Physics. These provide the fundamental content for future applications in specific disciplines, however it is common for students of such courses to feel unmotivated, since the teaching approach of these disciplines is, as a rule, theoretical and conceptual, not envisioning the application of the contents developed in class. In order to this scenario, in this article, we propose an approach to student digital authorship, through Digital Mathematical Performance in Differential and Integral Calculus discipline, in which students learn through the creation of digital media such as videos, e-books and Instagram posts, among others. The research follows the molds of a participant investigation in a qualitative approach. In this, it was observed that students feel more motivated, as well as consider that they obtain better learning when there is the possibility of using, manipulating, expressing themselves through the creation of digital media.
Keywords: digital mathematics performance; student authorship; calculus teaching; engineering